Impact of dispersive and nonlinear effects on pulse propagation in single-mode optical fibers - رزيقات, عصام; الزايز, ضهير الدين; بوشاري, سارة (University of El-Oued, 2022)
"So on this search We will discuss a group of fiber generalities its basic components (The core-Cladding - Buffer cladding - Buffer cladding ) and the function of each one of them and how the final form of fiber is formed and what it is made of (silicon dioxide (SiO 2 )) and what are its most important uses(Defense/Government -Telecommunications – Networking..) AND as second chapter will discuss Optical Fiber Effects The chromatic dispersion is considered an influential factor in the transmission of the signal through optical fibers, which is divided into two types: the single signal and the multiple signal. The multi-signal differs from the single signal by the number of transmitted color spectra, which causes the difference in the transmission distances between each of them. As we know, optical effects are divided into two types: linear and non-linear, which result in several types of different effects and special cases, including Kerr effect, Raman scattering and Brillwin scattering. the phiscal process can be represented by the Schrödinger equation pg. 3 particulary the The nonlinear Schrödinger equation in fiber optics or the Split-step Fourier method AND as Final chapter will discuss Simulation Results for the Most important Optical Fiber Effects Like Group-velocity dispersion and Chirped Gaussian pulses & Self-phase modulation & Optical solitons" "في هذا البحث سنناقش مجموعة من العموميات الألياف مكوناتها الأساسية ( الكسوة الأساسية - الكسوة العازلة - الكسوة العازلة) ووظيفة كل منها و كيف يتكون الشكل النهائي للألياف وما هي مكوناته (ثاني أكسيد السيليكون (SiO 2)) وماذا هي أهم استخداماته (الدفاع / الحكومة - الاتصالات - الشبكات ..) وكما سيناقش الفصل الثاني تأثيرات الألياف الضوئية يعتبر التشتت اللوني عاملاً مؤثرًا في إرسال الإشارة من خلال الألياف الضوئية ، والتي تنقسم إلى نوعين: الإشارة المفردة والمضاعفة الإشارة. تختلف الإشارة المتعددة عن الإشارة المفردة بعدد اللون المرسل الأطياف التي تسبب الاختلاف في مسافات الإرسال بين كل منها. مثل نعلم أن التأثيرات الضوئية تنقسم إلى نوعين: خطي وغير خطي مما ينتج عنه عدة أنواع من المؤثرات المختلفة والحالات الخاصة ، بما في ذلك تأثير كير ، تشتت رامان وتشتت بريلوين. يمكن تمثيل العملية المالية من خلال معادلة شرودنجر خاصة معادلة شرودنجر اللاخطية في الألياف الضوئية أو الانقسام خطوة فورييه طريقة كما سيناقش الفصل الأخير نتائج المحاكاة لأهم الألياف الضوئية تأثيرات مثل تشتت سرعة المجموعة ونبضات غاوس الزقزقة وتعديل الطور الذاتي و سوليتونات بصرية "
مذكرات ماستر تخصص اتصالات
Keywords: Optical fiber - Kerr Effect - Confinement Loss - Birefringence - Chromatic dispersion -Raman scattering -Brillouin scattering - Schrödinger equation - Split-step Fourier -Split-step Fourier - Third-order dispersion - Self-phase modulation -Pulse evolution - Second and higher-order solitons; الألياف الضوئية - تأثير كير - فقدان الحبس - الانكسار - التشتت اللوني - تشتت رامان - تشتت البريلوين - معادلة شرودنجر - الانقسام خطوة فورييه - الانقسام خطوة فورييه - التشتت من الدرجة الثالثة - تعديل الطور الذاتي - تطور النبض - الثاني وأعلى -